Construction of a physical fitness evaluation index system for excellent female Sanda athletes - Jiacheng Hu; Nan Zhang; Xiao Jin; Md Safwan Samsir; Yingying Cai; Xueqin Wang; Zuliana Bacho (e-VIBS, Faculty of Science and Natural Resources, 2024)
In this paper, primary, secondary and tertiary indicators are used to construct a physical fitness evaluation system for outstanding female Sanda athletes across three different weight categories: 48-52 kg, 56-65 kg, and 70-75 kg. The data are processed using box plot and standard deviation methods, and an evaluation model is developed by combining the analytic hierarchy process (AHP) with the entropy weight method. Finally, cluster analysis is applied for empirical evaluation. The study findings are as follows: (1) In the evaluation system, the highest-weighted indicators for the lightest category are general agility and specialized speed; for the middle category, specialized speed and 30-second leg raise; and for the heaviest category, 30-second leg raise and lower limb strength. (2) Lower-weight elite female kickboxers excel in speed; higher-weight elite female kickboxers excel in strength; and mid-weight elite female kickboxers excel in both. These indicators, along with a professional analysis of outstanding female Sanda athletes, are beneficial for coaches and athletes to design personalized training programs and competition tactics for fully exploring athletes' potential and enhancing their performances in competitions at different levels.